2022
DOI: 10.1007/s12010-022-04006-3
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Analysis of the Apoptotic and HPV Inhibitory Roles of Some Selected Phytochemicals Detected from the Rhizomes of Greater Cardamom

Abstract: Occurrence of cervical cancer, caused due to persistent human papilloma virus (HPV) infection, is common in women of developing countries. As the conventional treatments are expensive and associated with severe side effects, there is a need to find safer alternatives, which is affordable and less toxic to the healthy human cells. Present study aimed to evaluate the anti-HPV and apoptotic potential of four compounds from the greater cardamom ( Amomum subulatum Roxb. var. Golsey), namely r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 72 publications
0
25
0
Order By: Relevance
“…surface area) model, XlogP3 is an automistic method with correction factors [ 95 ]. All the molecules except for Astrakurkurone passed iLogP and XlogP3 criteria (range iLOGP: 0.19 to 4.37 and XlogP3: 1.48 to 6.19) [ 36 , 96 ]. All compounds were found to be water soluble (LogS).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…surface area) model, XlogP3 is an automistic method with correction factors [ 95 ]. All the molecules except for Astrakurkurone passed iLogP and XlogP3 criteria (range iLOGP: 0.19 to 4.37 and XlogP3: 1.48 to 6.19) [ 36 , 96 ]. All compounds were found to be water soluble (LogS).…”
Section: Resultsmentioning
confidence: 99%
“…PCA aids in the clustering of the given dataset based on the variables [ [97] , [98] , [99] , [100] ]. In our previous studies, we successfully employed the PCA tool as the primary step to cluster the compounds, thereby understand the mechanism of ligand-protein molecular interaction [ 36 , 101 ]. Similar to these studies, we found four clusters (C1–C4) in the PCA analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…RMSF values are utilized to calculate the atomic positional variation of each residue based on its C-alpha (Ca) atom. 72,73 The complexes NS2BNS3-taraxerol and NS5-apigenin under iMODS investigation have a signicant amount of deformability, according to the normal mode analysis. The low eigenvalue, covariance map, and elastic network of the complex under study are indications of the molecule's potential deformability and allowable dynamics.…”
Section: Discussionmentioning
confidence: 99%